(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Parkinsonism is characterised by bradykinesia, rigidity, and postural instability, leading to reduced hip flexion, a short shuffling gait, and an increased risk of falls. Although conventional therapy improves mobility, evidence on the effectiveness of task-specific hip flexion training is limited. This study aimed to examine the effects of task-specific hip flexion training on gait and motor performance in a patient with Parkinsonism. Case description and management: A 65-year-old man with idiopathic Parkinson’s disease underwent a four-week intervention comprising progressive hip flexion–specific exercises, including seated and standing hip flexion, step-ups, and stair climbing. Pre- and post-intervention assessments were conducted using the Unified Parkinson’s Disease Rating Scale (UPDRS III), Step Length, Cadence, and the Timed Up and Go (TUG) test. Post-intervention results showed improvements across all outcomes: UPDRS III score decreased from 38 to 28, step length increased from 28 cm to 42 cm, cadence improved from 82 to 96 steps/min, and TUG time decreased from 22 to 16 seconds. Conclusion: Task-specific hip flexion training effectively enhanced gait performance, stride efficiency, and motor control in Parkinsonism. The findings from this single case study are satisfactory and support the incorporation of hip flexion–focused exercises into physiotherapy rehabilitation.